2021
DOI: 10.1002/iub.2537
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress and NF‐kB activation in SARS‐CoV‐2 infected cells and their response to antiviral therapy

Abstract: Unfolded protein response (UPR) and endoplasmic reticulum (ER) stress are aspects of SARS-CoV-2-host cell interaction with proposed role in the cytopathic and inflammatory pathogenesis of this viral infection. The role of the NF-kB pathway in these cellular processes remains poorly characterized.When investigated in VERO-E6 cells, SARS-CoV-2 infection was found to markedly stimulate NF-kB protein expression and activity. NF-kB activation occurs early in the infection process (6 hpi) and it is associated with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 28 publications
(59 reference statements)
0
13
0
Order By: Relevance
“…ER stress is believed to induce activation of NF‐κB and pro‐inflammatory pathways (Figure 3). 46 It is perceived that overwhelmed protein folding within the ER triggers ROS generation, leading to activation of NF‐κB. ROS accumulation activates NF‐κB via alternative phosphorylation and degradation of IκBα (an inhibitor of NF‐κB) 47 .…”
Section: Molecular Links Between Er Stress and Inflammationmentioning
confidence: 99%
“…ER stress is believed to induce activation of NF‐κB and pro‐inflammatory pathways (Figure 3). 46 It is perceived that overwhelmed protein folding within the ER triggers ROS generation, leading to activation of NF‐κB. ROS accumulation activates NF‐κB via alternative phosphorylation and degradation of IκBα (an inhibitor of NF‐κB) 47 .…”
Section: Molecular Links Between Er Stress and Inflammationmentioning
confidence: 99%
“…ER stress and UPR have already been associated with SARS-CoV-2 infection in previous works [ 163 165 ]. Tang´s group found in 2021 that open reading frame 8 (ORF8) protein induces ER stress and UPR: cells transfected with either of the two different genotypes of ORF8 protein (ORF8L and ORF8S) had an increase in luciferase activity of reporter constructs driven by the promoters of GRP78 or GRP94, and mRNA levels of these two chaperones were upregulated too [ 166 ].…”
Section: Introduction: Covid-19 Cancer and Therapeutic Targetsmentioning
confidence: 91%
“…In 2022, Galli´s group demonstrated that SARS‐CoV‐2 infection in VERO‐E6 cells stimulated the expression of the ER stress signaling protein IRE‐1α [ 163 ], and that IRE‐1α activation in SARS‐CoV‐2 infected cells is associated with the inflammatory response (NF‐kB activation and pro‐inflammatory cytokine induction), which are key pathogenic events in COVID‐19. They also show that treatment with the antiviral Nelfinavir significantly reduced IRE‐1α activity of the infected cell, and restored homeostatic processes of the host cell.…”
Section: Introduction: Covid-19 Cancer and Therapeutic Targetsmentioning
confidence: 99%
“…IRE‐1α is associated with NF‐κB activation, and viruses promote self‐replication and inflammation through the interplay of IRE‐1α/UPR, NF‐κB, and MAPK pathways. 153 In addition, COVID‐19 induces dysregulation of STING (stimulator of IFN gene), which produces IFN‐β by activating IRF 3 or mediates the TBK/IKKε/NF‐κB pathway. 154 , 155 A review has summarized the role of crosstalk between NF‐κb and Nrf2‐Keap1 pathways on the neurological complications of COVID‐19.…”
Section: Inflammatory Pathways In Covid‐19mentioning
confidence: 99%
“…Virus–host cell interactions induce ER stress and ER stress signaling protein (IRE‐1α)/UPR signaling. IRE‐1α is associated with NF‐κB activation, and viruses promote self‐replication and inflammation through the interplay of IRE‐1α/UPR, NF‐κB, and MAPK pathways 153 . In addition, COVID‐19 induces dysregulation of STING (stimulator of IFN gene), which produces IFN‐β by activating IRF 3 or mediates the TBK/IKKε/NF‐κB pathway 154,155 .…”
Section: Inflammatory Pathways In Covid‐19mentioning
confidence: 99%